1998 Beaver Creek: level II Stream Survey - Nawa, Richard K.; Tioga Resources, Inc.; United States. Forest Service. Pacific Northwest Region (Southern Oregon University. Library, 1999)
A 13.66/2:B 42/3x 176 Cover title.; "May 1999."; Includes col. ill. and maps (some col.).; Photocopy. Ashland, Or.: Southern Oregon University, 2003. "The purpose of the survey was to quantify aquatic and riparian conditions. Beaver Creek is in Jackson County, Oregon about 9 miles south of Ruch . Headwaters are on Squaw Mountain. Except for the first 3/4 mile and isolated sections at its uppermost end, the stream is on the Rogue River National Forest in the Applegate Ranger District and Bureau of Land Management lands in the Medford District . The stream was divided into 5 reaches and surveyed upstream from its mouth for 7.5 miles. Logging, roads, water withdrawal, and loss of riparian vegetation associated with home building are land uses of concern. A key issue is high amounts of fine sediment in the stream channel . Coho salmon densities were low and distribution was spotty in the lower 1.7 miles of stream. Based on juvenile counts, a debris jam and an irrigation dam are suspected of having blocked coho salmon migration during winter 1997/1998. Moderate numbers of rainbow trout (probably offspring of steelhead) were found in the first 3 reaches of stream (5.2 miles). Rainbow trout densities in Reaches 4 and 5 were much lower (1.7 miles). No fish were observed above an 18 foot falls at stream mile 6.9. Three cutthroat trout were observed in a single pool in Reach 4" P. 2,5 [3,6].